Loss of nitrate reductases NIA1 and NIA2 impairs stomatal closure by altering genes of core ABA signaling components in Arabidopsis - Zhao, Chenchen (Plant Signal Behav, 2016)
Nitrate reductases NIA1 and NIA2 determine NO production in plants and are critical to abscisic acid (ABA)-induced stomatal closure. However, the role for NIA1 and NIA2 in ABA signaling has not been paid much attention in nitrate reductase loss-of-function mutant nia1nia2. Recently, we have demonstrated that ABA-inhibited K(+)(in) current and ABA-enhanced slow anion current were absent in nia1nia2. Exogenous NO restored regulation of these channels for stomatal closure in nia1nia2. In this study, we found that mutating NIA1 and NIA2 impaired nearly all the key components of guard cell ABA signaling pathway in Arabidopsis. We also propose a simplified model for ABA signaling in the nia1nia2 mutant.